Analisis Penerapan Standar Penilaian pada Sekolah Penyelenggara Kurikulum Merdeka - Siti Salamah, Ilma; Chandra Wiguna, Arya; Taufiqul Hakim, Rifqi; Putri A. L. Fajar, Rizka; Prihantini (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
The research aims to determine the application of assessment standards in schools implementing the independent curriculum. The method used in this research is a descriptive qualitative method to describe in depth the implementation of educational assessment standards that have been implemented. This assessment uses subjects from the principal and one of the homeroom teachers at SDIT Daarul Huda. Data collection techniques and tools in this research were carried out through observation of the school environment, interviews conducted with school principals and teachers, documentation in photo or video format during research activities. The results of the research show that the implementation of assessment standards at Daarul Huda Elementary School can be said to be going well and in accordance with the standards of the Minister of Education and Culture.